2005
DOI: 10.1016/j.peptides.2004.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Central vagal stimulation activates enteric cholinergic neurons in the stomach and VIP neurons in the duodenum in conscious rats

Abstract: The influence of central vagal stimulation induced by 2h cold exposure or intracisternal injection of thyrotropin-releasing hormone (TRH) analog, RX-77368, on gastro-duodenal enteric cholinergic neuronal activity was assessed in conscious rats with Fos and peripheral choline acetyltransferase (pChAT) immunoreactivity (IR). pChAT-IR was detected in 68%, 70% and 73% of corpus, antrum and duodenum submucosal neurons, respectively, and in 65% of gastric and 46% of duodenal myenteric neurons. Cold and RX-77368 indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 40 publications
2
45
0
Order By: Relevance
“…As mentioned earlier, pChAT antiserum has been used to visualize intramural cholinergic neurons throughout the gastrointestinal tract in the rat (Nakajima et al, 2000;Tooyama and Kimura, 2000;Yuan et al, 2005Yuan et al, , 2007Miampamba et al, 2007), mouse (Wang et al, 2007), guinea-pig (Nakajima et al, 2000;Chiocchetti et al, 2003), sheep (Chiocchetti et al, 2004;Mazzuoli et al, 2007) and pig (Brehmer et al, 2004). Following the preliminary study in the myenteric plexus of the rat duodenum a more detailed study indicated that pChAT-positive cell bodies were present in every myenteric and submucosal ganglion throughout the entire extent of the gastrointestinal tract (Nakajima et al, 2000).…”
Section: Pchat a Cholinergic Marker For The Enteric Nervous Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned earlier, pChAT antiserum has been used to visualize intramural cholinergic neurons throughout the gastrointestinal tract in the rat (Nakajima et al, 2000;Tooyama and Kimura, 2000;Yuan et al, 2005Yuan et al, , 2007Miampamba et al, 2007), mouse (Wang et al, 2007), guinea-pig (Nakajima et al, 2000;Chiocchetti et al, 2003), sheep (Chiocchetti et al, 2004;Mazzuoli et al, 2007) and pig (Brehmer et al, 2004). Following the preliminary study in the myenteric plexus of the rat duodenum a more detailed study indicated that pChAT-positive cell bodies were present in every myenteric and submucosal ganglion throughout the entire extent of the gastrointestinal tract (Nakajima et al, 2000).…”
Section: Pchat a Cholinergic Marker For The Enteric Nervous Systemmentioning
confidence: 99%
“…Moreover, pChAT has been used as a marker for enteric cholinergic neurons in physiological studies of rat and mouse. These studies have demonstrated that enteric pChAT neurons containing the nuclear protein Fos, a marker for cellular activation, were activated following stress induced by cold (Yuan et al, 2005) and water avoidance (Miampamba et al, 2007), and pharmacological manipulations with a thyrotropin-releasing hormone analog (Yuan et al, 2005), serotonin (Wang et al, 2007) and corticotropin releasing factor .…”
Section: Pchat a Cholinergic Marker For The Enteric Nervous Systemmentioning
confidence: 99%
“…Anterograde tracing studies using Phaseolus vulgaris-leucoagglutinin (Pha-L), a carbocyanine dye, or wheat germ agglutinin conjugated horseradish peroxidase (WGA-HRP) have reported that the neurons in the myenteric ganglia in the stomach receive fibers and terminals from the DMV neurons [5][6][7] . Since stimulation of neuron in the DMV activated the motility and secretions of the stomach 8,9) , single vagal motor neurons are thought to regulate the motility of the gastrointestinal tract by way of the myenteric ganglion neurons. Thus, it is likely that single neurons in the DMV send collateral fibers to the stomach, the duodenum, and the small and the large intestines.…”
Section: Introductionmentioning
confidence: 99%
“…This is in part due to the various technical limitations that make the visualization of cholinergic structures by histochemical means challenging. Cholinergic markers have been widely used to label cholinergic cells, axons, and terminals in peripheral tissues (Anlauf et al, 2003; Arvidsson et al, 1997; Bellier and Kimura, 2011; Schafer et al, 1998; Weihe et al, 1996; Yuan et al, 2005), but their lack of sensitivity has repeatedly been noted. Among other examples, the detection of cholinergic markers in the intestinal mucosa is variable in the rat (Ratcliffe et al, 1998; Schafer et al, 1998) and indicate only modest innervation in the mouse (Mongardi Fantaguzzi et al, 2009), despite the known cholinergic innervation to this tissue.…”
mentioning
confidence: 99%